LEARNING ENGLISH THROUGH SOCIAL MEDIA IN INDONESIA - IKA TRISNANTASARI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2017)
This research describes how to learn English through social media especially in Indonesia. As all the people needs, social media is one of the essencial part in every single creature in this world. Although not all human uses social media, but almost all the people tested or to be apart in social media. Unfortunetely there is no legal law to protect legality in social media, it means that social media is wild media that not reflecting in the real life. A good user of social media also have a positive impact on cyberspace. Therefore learning English through social media is one of a good ways as a user in social media. Through social media, the educators must update their ways in teaching learning process especially in teaching English.